Formation and Identification of Six Amino Acid - Acrylamide Adducts and Their Cytotoxicity Toward Gastrointestinal Cell Lines - Li, Dan; Xian, Fangfang; Ou, Juanying; Jiang, Kaiyu; Zheng, Jie; Ou, Shiyi; Liu, Fu; Rao, Qinchun; Huang, Caihuan (Frontiers in Nutrition, 2022)
Acrylamide (AA) is a food contaminant, and amino acids are suggested to mitigate it by forming adducts. The emergence of acrylamide adducts may cause underestimation of acrylamide exposure level as well as trigger new safety problems. Based on the acrylamide elimination capability of four amino acids, this study chemically synthesized six amino acid-acrylamide adducts. Their structures were analyzed, followed by content determination in 10 commercially baking foods. The Michael adducts formed by one molecule of γ-aminobutyric acid (GABA) and acrylamide was most abundant in foods among six adducts. Furthermore, it markedly decreased the cytotoxicity of acrylamide in Caco-2 cells and GES-1 cells. This finding suggests that amino acids can be used to reduce acrylamide level in processed foods and mitigate its hazardous effects after intake.